Methamphetamine mediates immune dysregulation in a murine model of chronic viral infection - Sriram, Uma; Haldar, Bijayesh; Cenna, Jonathan M.; Gofman, Larisa; Potula, Raghava (Frontiers in Microbiology, 2015)
Methamphetamine (METH) is a highly addictive psychostimulant that not only affects the brain and cognitive functions but also greatly impacts the host immune system, rendering the body susceptible to infections and exacerbating the severity of disease. Although there is gathering evidence about METH abuse and increased incidence of HIV and other viral infections, not much is known about the effects on the immune system in a chronic viral infection setting. We have used the lymphocytic choriomeningitis virus (LCMV) chronic mouse model of viral infection in a chronic METH environment and demonstrate that METH significantly increases CD3 marker on splenocytes and programmed death -1 (PD-1) expression on T cells, a cell surface signaling molecule known to inhibit T cell function and cause exhaustion in a lymphoid organ. Many of these METH effects were more pronounced during early stage of infection, which are gradually attenuated during later stages of infection. An essential cytokine for T-lymphocyte homeostasis, Interleukin-2 (IL-2) in serum was prominently reduced in METH-exposed infected mice. In addition, the serum pro-inflammatory (TNF, IL12 p70, IL1β, IL-6 and KC-GRO) and Th2 (IL-2, IL-10 and IL-4) cytokine profiles were also altered in the presence of METH. Interestingly CXCR3, an inflammatory chemokine receptor, showed significant increase in the METH treated LCMV infected mice. Similarly, compared to only infected mice, epidermal growth factor receptor (EGFR) in METH exposed LCMV infected mice were up regulated. Collectively, our data suggest that METH alters systemic, peripheral immune responses and modulates key markers on T cells involved in pathogenesis of chronic viral infection.